Developing the Interface of HaoSpace Mood Tracking Application Using Design Thinking - Desak Putu Mahadewi Saraswati; Ketut Agus Seputra; Luh Joni Erawati Dewi (Journal of Information System Research (JOSH), 2025)
Mental health problems, particularly mood disorders, remain a major concern among adolescents and young adults, as they can affect academic performance, social interactions, and emotional well-being. Despite growing awareness, many adolescents still lack accessible tools to effectively monitor and manage their moods. The objective of this research is to design and develop a prototype of a mood tracking application called “HaoSpace” to address this gap. The research employed the Design Thinking methodology, which emphasizes a user-centered approach and involves five stages: empathize, define, ideate, prototype, and test, with participants consisting of students, workers, and a psychology expert. The resulting prototype includes features such as journaling, reminders, daily reports, and interactive visualizations in the form of graphs and mood-based calendars to facilitate self-monitoring and reflection. User testing showed positive responses regarding navigation, interface design, and feature relevance, while the psychology expert assessed the prototype as a feasible tool for self-reflection and emotional regulation among adolescents and young adults. In conclusion, HaoSpace demonstrates potential as a digital intervention to enhance mood awareness and promote mental well-being among adolescents and young adults.